2017
DOI: 10.1021/acs.iecr.6b04650
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Highly Stable Superhydrophobic Surface with Dual-Scale Structure and Its Antifrosting Properties

Abstract: The stable superhydrophobic aluminum alloy surface with dual geometric architectures was prepared by a combination of simple processes of chemical etching, dip-coating, and modification of fluorosilicone. The Al surface with 20 min of acid etching and nanosilica dip-coating has the best superhydrophobicity, which showed water contact angles (WCAs) of >157° and water sliding angles (SAs) of <1°. The superhydrophobic surface showed excellent antifogging, antifrosting, and delayed icing performances, compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 54 publications
1
35
0
Order By: Relevance
“…Superhydrophobic surfaces with low contact angle hysteresis are also termed water‐repellent surfaces . Water‐repellent surfaces offer great potential for developing surfaces with antifogging and anti‐icing functions …”
Section: Discovery: Natural Surfacesmentioning
confidence: 99%
“…Superhydrophobic surfaces with low contact angle hysteresis are also termed water‐repellent surfaces . Water‐repellent surfaces offer great potential for developing surfaces with antifogging and anti‐icing functions …”
Section: Discovery: Natural Surfacesmentioning
confidence: 99%
“…As shown in the Figure 3 , the characteristic peaks of curves b and c can be observed in the FTIR spectrum of PMETAC-PTSPM/SiO 2 -NH 2 . The results of infrared spectroscopy indicate the synthesis of the polymer and the successful introduction of amino-modified SiO 2 in the polymer [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the water droplet floats on the superhydrophobic surface and it comes into contact with this only for a small area. This leads to a reduction in both heat exchange and the ice nucleation rate [42][43][44]. Moreover, it is well reported that in SHP coatings, the air pockets further hinder the freezing process by acting as heat insulators [45,46], delaying the heat exchange.…”
Section: Anti-icing Propertiesmentioning
confidence: 99%